2022
DOI: 10.1128/spectrum.02487-22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Microbial Identification of Severe Oral Infections by MALDI-TOF Mass Spectrometry in Stockholm County: an 11-Year (2010 to 2020) Epidemiological Investigation

Abstract: Oral diseases and associated microbes are a risk factor for systemic diseases and can change the courses of these diseases. To date, epidemiological data on microbial oral infections are scarce, and longitudinal reports are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These bacteria are well-recognized for causing central nervous system infections, and in recent decades, the incidence of CAs with SAG bacteria has increased [25]. They are often isolated from odontogenic infectious lesions including periapical abscesses, periodontal abscesses, and pericoronitis [26][27][28][29][30]. Also, S. constellatus and S. intermedius found in dental plaque have been associated with the development of periodontal disease [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bacteria are well-recognized for causing central nervous system infections, and in recent decades, the incidence of CAs with SAG bacteria has increased [25]. They are often isolated from odontogenic infectious lesions including periapical abscesses, periodontal abscesses, and pericoronitis [26][27][28][29][30]. Also, S. constellatus and S. intermedius found in dental plaque have been associated with the development of periodontal disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Also, S. constellatus and S. intermedius found in dental plaque have been associated with the development of periodontal disease [ 31 ]. A recent study from Sweden concluded that S. anginosus alone, as a single species, accounted for over 20% of oral bacterial infections [ 30 ], and a previous study showed a very close similarity between brain and oral isolates of SAG in a CA patient with periodontitis, where the use of highly discriminative phenotypic and genetic fingerprint techniques could not exclude that microorganisms involved in CA formation came from the periodontal pocket [ 32 ]. However, it is important to bear in mind that microorganisms from the SAG, especially S. anginosus , are commonly isolated from gastrointestinal and genitourinary tract infections as well [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various phenotypic screening tools based on biochemical properties, such as API ID32C and AuxaColor, are commercially available [33][34][35][36] as well as automated metabolic characterisation facilities, i.e., VITEK 2 and Biolog's Omnilog System [37,38]. Recently, MALDI-TOF mass spectrometry (based on the comparison of protein mass spectra with well-characterised reference strains included in reliable databases) is proving to be a commonly used methodology for microbial (mainly bacterial) identification, especially in the clinical fields but also in commercial sectors [39][40][41].…”
Section: Microbial Resources and Service Supplymentioning
confidence: 99%
“…Once pulp vitality becomes dysfunctional, the pulp degenerates and may be invaded by microorganisms, eventually leading to total necrosis [ 14 ]. Depending on the host defense response and the degree of microbial virulence and their byproduct, untreated pulpal infection may also spread beyond the root apex, leading to periapical pathosis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%